The Impact of the Project-Based Learning (PjBL) Model Assisted by Liveworksheet Media on Critical Thinking Skills of Vocational High School Students - Rika Defira; Asrul Huda; Muhammad Anwar; Ambyar Ambyar (Postgraduate, University of Mataram, 2024)
This study investigates the effectiveness of the Project-Based Learning (PjBL) model integrated with Liveworksheet media in enhancing the critical thinking skills of vocational high school students. Employing a true experimental design with a pretest- posttest control group approach, the research compared two groups: the experimental group using PjBL with Liveworksheet and the control group receiving conventional instruction. Data collected from pretest and posttest assessments revealed that the experimental group demonstrated a significant improvement in critical thinking skills, with an average posttest score of 81, compared to 64 in the control group. The pretest scores showed no significant differences between the groups, indicating a similar starting point. Post-intervention results were analyzed using statistical tests, confirming the normal distribution and equal variances of data. The hypothesis testing further validated a substantial difference in critical thinking skills, favoring the PjBL model with Liveworksheet media. These results underscore the effectiveness of this innovative teaching approach in fostering critical thinking skills among vocational students